A study on MUSULMAN brand awareness among residents in Section 8 Shah Alam Selangor / Azlin Mohd Kassim - Mohd Kassim, Azlin (1998)
MUSULMAN SDN. BHD (MSB) is a growing Malay retailer introducing Muslim fashion apparels to Muslim women and also for non-Muslim women who want to have descent apparels. As to increase their sales, brand awareness among people is very important. People do not buy the brand name product, if they are not being familiarized or being aware with the brand existence. The study objectives comprises of determining level of MUSULMAN brand awareness among residents in Section 8 Shah Alam. Secondly the degree of awareness on design and style, price, colour, selection in apparels and fabric or materials of MUSULMAN. Third, to determine which promotional tools are most effective in promoting MUSULMAN to the public. From the study, it was found that MSB should promote more on its brand because out of 100 respondents, 69 of them are aware with the brand. Therefore to increase more awareness, they should implement an effective promotional tools.